Turning the FeFe hydrogenase from Clostridium beijerinckii into an efficient H 2 oxidation catalyst using a redox-active matrix - Dawit T. Filmon; Jan Jaenecke; Martin Winkler; Vincent Fourmond; Christophe Léger; Nicolas Plumeré (Proceedings of the National Academy of Sciences, 2025)
Hydrogenases are Nature’s sustainable and efficient catalysts for the conversion between H + and H 2 . The obstacles that prevented their use as H 2 oxidation catalysts in fuel cells are being removed one by one, thanks to the continuous discovery of hydrogenases that have unexpected catalytic properties, the development of new methods for their scalable production and matrices that protect them. Obtaining an efficient biohybrid electrode that is scalable and robust under a large range of experimental conditions is still challenging. The FeFe hydrogenase of Clostridium beijerinckii is a very active catalyst of H 2 evolution and can be handled under O 2 , and its production can potentially be scaled up. However, it was believed that it cannot be used for H 2 oxidation, as it is easily oxidized to an O 2 -stable but inactive state. Here, we show that when the enzyme is embedded into a redox-active film whose reduction potential is finely tuned to the equilibrium potential of the H + /H 2 couple, the potential that the enzyme experiences can be buffered in a sharp window that is actually compatible with enzyme-catalyzed H 2 oxidation and prevents anaerobic inactivation. This leads us to provide the demonstration of an FeFe hydrogenase-based system that can be used for H 2 oxidation and that can be repeatedly exposed to O 2 during and between operational cycles.